2015
DOI: 10.1002/bip.22714
|View full text |Cite
|
Sign up to set email alerts
|

Folding propensity of anoplin: A molecular dynamics study of the native peptide and four mutated isoforms

Abstract: Anoplin, a cationic decapeptide amide GLLKRIKTLL-NH2 derived from venom sac of the solitary wasp Anoplius samariensis has been investigated through Molecular Dynamics. The wild-type (WT) and four isoforms were simulated both in water and in the membrane-mimicking solvent trifluoroethanol (TFE). In water all the investigated species, found to be in rapid equilibrium between different conformational states, can be considered as unfolded. On the other hand, in TFE all the systems enhance their rigidity and, in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In particular, anoplin and decoralin have lengths of only 10 and 11 amino acids, respectively, with virtually no hemolytic activity. There are many studies based on these peptides towards developing new antibiotic and anticancer agents [30,31,32,33,34,35,36,37,38,39,40,41,42,43,57,58,59,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, anoplin and decoralin have lengths of only 10 and 11 amino acids, respectively, with virtually no hemolytic activity. There are many studies based on these peptides towards developing new antibiotic and anticancer agents [30,31,32,33,34,35,36,37,38,39,40,41,42,43,57,58,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…This is among the smallest antimicrobial peptides with an α-helical structure found from natural sources, which can be advantageous for structural modification, structure-activity relationships studies, and therapeutic applications as a new and useful antimicrobial agent. There are many studies along this line [30,31,32,33,34,35,36,37,38,39,40,41,42,43].…”
Section: Chemical and Biological Characterizationmentioning
confidence: 99%
“…Previous work from our laboratories has reported molecular dynamics (MD) studies on a number of short natural peptides whom antimicrobial activity is strictly related to their amphipathic character, net positive charge and their propensity to adopt α‐helical conformation in hydrophobic solvent . In this paper, we focused our interest on crabrolin, a 13‐residue peptide whose sequence is FLPLILRKIVTAL‐NH 2 that has been found in the venom of European hornet Vespa crabro , amidated at C‐terminus and with a net positive charge of +2/+3 at neutral pH, rich in hydrophobic aminoacids.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, positively charged residues (Arg and Lys) were shown to be important since they promote electrostatic attraction with the negatively charged bacterial membrane [23,24]. Through the structure-function analysis of short natural peptides we have shown that their antimicrobial activity depends on the amphipathic character, the net positive charge and the propensity to adopt α-helical conformation in hydrophobic solvent [25][26][27][28][29]. In our previous study, we analyzed a short peptide, Crabrolin, consisting of 13 aminoacids (sequence FLPLILRKIVTAL-NH 2 ), originally found in the venom of European hornet Vespa crabro, with a net positive charge of +2/+3 at neutral pH, rich in hydrophobic amino acids [30], previously studied by Argiolas et al [31].…”
Section: Introductionmentioning
confidence: 99%